DEVELOPMENT OF MONTESSORI BASED-MULTIPLICATION PROPS FOR ELEMENTARY SCHOOL - Maryam Faizah; Putri Nur Faizah; Muhammad Syahru Romadhon; Rena Widayanti (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2023)
Abstract This study aims to describe the procedure of developing multiplication teaching props based on the Montessori method and to analyze students' responses to the Montessori multiplication props. Research and Development method through the ADDIE model was used in this research. The subjects of this study were 28 second-grade students at MIN 1 Malang City. Data collection was employed through questionnaires, interviews, observations, and documentation. Data analysis techniques encompassed both quantitative and qualitative data analysis. This research resulted in Montessori-based multiplication teaching props. The validation result of media products met very valid criteria, with scores of 80 from the material validator, 94 from the media design validator, and 86 from the expert validator. This media is equipped with components that are easy to understand and easy to use, as students scored 81% with positive criteria. Therefore, it can be concluded that students responded positively to the Montessori-based multiplication teaching props as a tool for mathematics learning.